Hvilke strategier anvender dagtilbudsledere for at undgå mangel på arbejdskraft: de mest virkningsfulde, passende eller praktisk mulige? - Munkedal, Søren (Tidsskrift for Professionsstudier, 2025)
Like many other European countries Early Childhood Education in Denmark is challenged with a shortage of preschool teachers. More than eight out of ten directors or managers of daycare centers believe that labor supply is one of the most important challenges for their center in the years to come. However, research on recruitment practices at the local level is lacking. Based on a survey among 1,063 Danish daycare managers as well as qualitative interviews with six managers this article investigates which measures Danish daycare centers take to have sufficient human resources in the future and tries to understand these choices through three different theoretical perspectives. Although managers’ use of measures depend on their perception of these measures’ effectiveness, a ‘logic of consequentiality’ can only partly explain the recruitment practices. This understanding must be supplemented with a ‘logic of appropriateness’ since managers’ strategies are shaped by external demands and expectations. Finally, many recruitment practices can be understood in terms of a ‘logic of practice’ or ‘wayfinding’.